Behcet’s-like disease induced by secukinumab in a patient with psoriasis: a case report and literature review - Kecen Liu; Jingru Sun (Journal of Dermatological Treatment)
Purpose: The incidence of cutaneous paradoxical reactions associated with IL-17 inhibitors has gained attention in recent literature. Our report aims to investigate the characteristics of one rare paradoxical reaction, presenting as Behcet’s disease.Methods: We reported one case of Behcet’s-like disease induced by secukinumab in a patient with psoriasis. This patient, a young woman with a long history of psoriasis, showed significant improvement in her psoriatic condition after receiving four doses of secukinumab. Unexpectedly, she developed symptoms such as high fever, painful oral and genital ulcers, facial maculopapules, and erythema nodosum-like lesions on her lower limbs. Despite neutrophilia, there was no evidence of infection found in her laboratory tests. Histological analysis of a skin biopsy highlighted subcutaneous panniculitis and a mixed inflammatory cell infiltrate in the dermis. The patient was consequently diagnosed with secukinumab-induced Behcet’s-like disease. Additionally, we have reviewed nine other documented cases of Behcet’s-like disease triggered by IL-17 inhibitors.Results: This group showed no significant gender preference, suffering from conditions such as psoriasis, ankylosing spondylitis, and hidradenitis suppurativa. Oral and genital ulcers were prevalent among the paradoxical reactions noted. Marked improvement was observed in all patients upon discontinuation of the IL-17 inhibitors.Conclusions: Our report serves to alert physicians to this uncommon but significant paradoxical effect that may arise with anti-IL-17 treatment.